Integrated coastal and ocean management : - Cicin-Sain, Biliana (Island Press, 1998)
Biliana Cicin-Sain and Robert W. Knecht are co-directors of the Center for the Study of Marine Policy at the University of Delaware in Newark, Delaware and co-authors of The Future of U.S. Ocean Policy (Island Press, 1998).